Projecting the need for and cost of long term care for older persons. - Holmes, Wendy (Sustainable development working papers.)
With the numbers of older persons in the Asia and Pacific region increasing rapidly, there is a growing urgency to develop and strengthen LTC support systems and services. The paper first outlines modeling and its importance. Second, it describes key concepts related to LTC need, demand, and measurement. Then, it identifies key issues to consider when designing and using models. A review of recent modeling studies is also summarized, drawing out lessons relevant to low- and middle- income countries.